Compact Wideband Broadside-Coupled Microstrip-Slot Bandpass Filter for Communication Applications - Norhudah Seman; Dyg Norkhairunisa Abang Zaidel; Zuhaili Amalina Abd. Wahid; Nor Azimah Mohd Shukor; Tharek Abd Rahman (Institute of Advanced Engineering and Science, 2017)
This paper proposes a compact size design of wideband bandpass filter (BPF). The broad-side coupling microstrip-slot technique is used to accomplish a good passband response with very low insertion loss across a wideband frequency range. The BPF that is designed using Rogers RO4003C substrate shows a good performance with the respective maximum reflection coefficient and insertion loss of -10 dB and 1.2 dB between 0.92 GHz and 5 GHz. This type of BPF filter is useful in any communication applications.